The Reconstruction of The Corruption Eradication System in The Perspective of The Criminal Law in Indonesia - Tinuk Dwi Cahyani; Nu'man Aunuh (Alliance of Health Activists (AloHA), 2020)
Corruption is a crime, just like all other crimes which has existed since a long time ago. The problem is that corruption is like a virus in the society which may spread very quickly. It is difficult to eradicate. The efforts to eradicate corruption has been carried out, but the reality shows that it keeps on increasing along with the increasing welfare, technologies, and development. On 2018, Indonesia stood in the 89th place of the world corruption rank. Thus, there needs to be a reconstruction to the forms of the main and the additional punishments in Indonesia’s positive law, so that it is clear that corruption is a terrible crime which must be fought using extraordinary methods. In Indonesia’s constitution of Corruption Eradication Article 2 clause 2 of the constitution No. 31 of 1999 it states that, “In the case of the crime of corruption as meant in clause (1), when carried out under certain conditions, death penalty may be imposed.” From the explanation of that article, and also from the Constitution No. 31 of 1999 it can be concluded that the forms of existing main punishments are: Imprisonment for some time or life sentence, death sentence, or fine. Meanwhile, the forms of additional punishments are: The revocation of certain rights, the deprivation of certain items, the announcement of the judge’s verdict, the deprivation of tangible movable properties (unmovable and intangible) which are used or are obtained from corruption, the payment of replacement money according to the amount obtained from corruption, the closing of some businesses for the maximum period of one year, and the revocation of all or some rights (the elimination of some privileges. Keywords: reconstruction; corruption; criminal law